Constraints to sheep and goat production in smallholder mixed farms in Kenya's central highlands - Odoi, A.; Gathuma, J.M.; Gachuiri, C.K.; Omore, Amos O.; Gitau, T.; Wanyangu, S.W.; Murage, E. (International Society for Veterinary Epidemiology and Economics, 2000)
Small ruminants play an important, but often underestimated, role in the livelihoods of resource-poor farmers in Kenya. Besides being an important source of protein and immediate cash, they also have a variety socio-cultural values. Their importance in mixed crop-livestock systems in Kenya is expected to increase in the future with diminishing land sizes but specific constraints to their production in this system are largely undocumented. The aim of this study was to investigate the general constraints to production of small ruminants in smallholder mixed farms in Kenya's Central Highlands.